Full-fat dairy products and cardiometabolic health outcomes: Does the dairy-fat matrix matter? - Taormina, Victoria M.; Unger, Allison L.; Kraft, Jana (Frontiers in Nutrition, 2024)
Reducing dairy fat intake is a common dietary guideline to limit energy and saturated fatty acid intake for the promotion of cardiometabolic health. However, research utilizing a holistic, food-based approach to assess the consumption of the fat found in dairy, a broad and diverse food group, may provide new insight into these guidelines. Dairy fat is comprised of a diverse assembly of fatty acids, triacylglycerols, sterols, and phospholipids, all uniquely packaged in a milk fat globule. The physical structure of this milk fat globule and its membrane is modified through different processing methods, resulting in distinctive dairy-fat matrices across each dairy product. The objectives of this narrative review were to first define and compare the dairy-fat matrix in terms of its unique composition, physical structure, and fat content across common dairy products (cow's milk, yogurt, cheese, and butter). With this information, we examined observational studies and randomized controlled trials published within the last 10 years (2013-2023) to assess the individual effects of the dairy-fat matrix in milk, yogurt, cheese, and butter on cardiometabolic health and evaluate the implications for nutrition guidance. Searches conducted on Ovid MEDLINE and PubMed® utilizing search terms for cardiometabolic health, both broadly and regarding specific disease outcomes and risk factors, yielded 59 studies that were analyzed and included in this review. Importantly, this review stratifies by both dairy product and fat content. Though the results were heterogenous, most studies reported no association between intake of these individual regular-fat dairy products and cardiometabolic outcome measures, thus, the current body of evidence suggests that regular-fat dairy product consumption may be incorporated within overall healthy eating patterns. Research suggests that there may be a beneficial effect of regular-fat milk and yogurt intake on outcome measures related to body weight and composition, and an effect of regular-fat cheese intake on outcome measures related to blood lipids, but more research is necessary to define the directionality of this relationship. Lastly, we identify methodological research gaps and propose future research directions to bolster the current evidence base available for ascertaining the role of dairy fat in a healthy diet.